Evaluarea riscului pentru starea de sănătate a populației în funcție de compoziția apei potabile (One Health & Risk Management, 2020)
Introduction. Drinking water includes a multitude of natural elements, with a strong connection between them, which through the dynamics of their modification in many cases influence the health of the population.Material and methods. The quality of drinking water from the Prut river ecosystem was studied (water from aqueducts fed from the river, water from artesian wells, water from adjacent wells), health status of the population from riparian localities (Lipcani, Ungheni and Cahul). The correlations between these two indicators and the risk of population disease caused by water quality were calculated. Hygienic, epidemiological, sanitary-chemical and statistical methods of investigation were used.Results. Following the study, the existence of small and medium correlative dependencies between the water quality indices from the aqueduct fed from the Prut River and the prevalence of the main groups of nosology of morbidity was highlighted. High direct correlative dependencies of health indices on water quality in artesian wells and wells were quantified. The values of the risk of genito-urinary, osteo-articular, digestive system, blood diseases/anemia, etc. were determined.Conclusions. Finally, there was a causal relationship between the factors investigated and the health of the population, highlighting the risk of developing nosological forms.
Keywords: sanitary-chemical indicators of water; population morbidity; correlation; risk